2003
DOI: 10.1007/s00063-003-1253-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetts�ureinduzierte -Zell-Apoptose

Abstract: FFAs exert different effects on beta-cell survival. Saturated FFAs turned out to be pro-apoptotic, whereas unsaturated FFAs protected from saturated FFA-induced apoptosis. Furthermore, our data suggest an involvement of PKC-delta in apoptosis induced by saturated FFAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, recent reports have demonstrated that the ability of fatty acids to cause apoptosis in the rat ␤-cell line RIN1046-38 and human islets is dependent on the degree of saturation. Whereas palmitic acid and stearic acid were pro-apoptotic when used at 1 mM for 24 h, linoleic acid, palmitoleic acid, and oleic acid did not cause apoptosis and actually protected the ␤-cells from apoptosis resulting from incubation with saturated fatty acids (35). Because a large range of both saturated and unsaturated fatty acids are agonists for GPR40, the primary role of the receptor may therefore not be mediation of the apoptotic effects of fatty acids.…”
Section: Fatty Acids As Ligands For Gpr40mentioning
confidence: 99%
“…However, recent reports have demonstrated that the ability of fatty acids to cause apoptosis in the rat ␤-cell line RIN1046-38 and human islets is dependent on the degree of saturation. Whereas palmitic acid and stearic acid were pro-apoptotic when used at 1 mM for 24 h, linoleic acid, palmitoleic acid, and oleic acid did not cause apoptosis and actually protected the ␤-cells from apoptosis resulting from incubation with saturated fatty acids (35). Because a large range of both saturated and unsaturated fatty acids are agonists for GPR40, the primary role of the receptor may therefore not be mediation of the apoptotic effects of fatty acids.…”
Section: Fatty Acids As Ligands For Gpr40mentioning
confidence: 99%
“…Chronic treatment with high physiological levels of saturated FA, but not with mono-or polyunsaturated FA, triggers apoptosis in about 20% of cultured b-cells [94]. Chronic treatment with high physiological levels of saturated FA, but not with mono-or polyunsaturated FA, triggers apoptosis in about 20% of cultured b-cells [94].…”
Section: Molecular Mechanismsmentioning
confidence: 99%